Comparison of maternal and neonatal profiles and outcomes between referred and self-referred patients delivered at the Ganyesa District Hospital - Mosedi, Abigail Thumeka (My University, 2012)
BACKGROUND: Maternal health care in South Africa is based on the District Health System model which includes public health facilities (such as primary health care clinics, community health centers and district hospitals) as well as private health facilities. The majority of uncomplicated deliveries are expected to happen at community health centers and only complicated cases are expected to be referred to district hospitals. But in reality, the majority of deliveries in a health district happen in district hospitals. This often results in increasing utilisation of resources and decreased quality of care at these hospitals. The Ganyesa District Hospital, situated in Dr Ruth Segomotsi Mompati District in the North West Province has been facing similar challenges. Although the Hospital has been collecting routine information for the District Health Information System, it has never been analysed systematically to understand the impact of the current referral system on the performance of this Hospital. Aims: To compare maternal and neonatal profiles and outcomes between referred and self-referred patients delivered at the Ganyesa District Hospital during one year study period (1st April 2008 to 31st March 2009). Methodology: The setting of this study was Ganyesa District Hospital, in the Dr Ruth Segomotsi Mompati District in the North West Province. A Cross sectional study design was used utilising retrospective data, from the Hospital information systems. The MS excel software based data extraction tool was designed to obtain data from Hospital Information System. The variables used for this study included socio-demographic and clinical profiles of patients. A comparative statistical analysis were done to compare the profile of two groups of patients: (Referred and Self-referred) Results: The majority of the subjects were black. Most of the patients were, single and unemployed. The majority of the patients were multigravidae. The most common past and current medical disorders were diabetes and pregnancy induced hypertension (PIH). The prevalence of pre-term deliveries of the subjects was 14.8%. The majority of the subjects delivered normally (86.5%) followed by CS (13.2%). The majority of CSs were performed as emergency. PIH and previous CS were common maternal indications whereas fetal distress and mal-presentation were common fetal indications. Prolonged labour and Intra-partum haemorrhage were common maternal complications whereas fetal distress and fresh still-birth were common fetal complications. There were 26 (4.3%) post-partum maternal complications. There were 3 (4.6%) deaths during this period among the patients (Maternal mortality rate of 501/ 100,000). The incidence of low birth weight (less than 2.5 kg) was 23%. The fresh and macerated stillbirths and low Apgar score were common neonatal complications. The majority of the patients (374, 62.5%) arrived after-hours. The majority of the patients arrived by ambulance (87.3%). The median distance between places of residence and PHC facilities (Clinic and CHC) was 12 km. The median distance between places of residence and the Hospital was 45 km. There were no significant differences in socio-demographic (age, ethnicity, marital and employment status) and obstetric profiles (gravidity, prevalence of past medical disorders and antenatal disorders, prevalence of pre-term deliveries, mode of deliveries, intra-partum or post-partum complications and maternal outcomes.) between referred and self-referred patients. The two groups were not significantly different in terms of birth weight, the incidence of low birth weight, and Apgar scores (at 1 minute and 10 minutes) and neonatal complications. More referred patients arrived after hours in comparison to self-referred patients More referred patients arrived with ambulance in comparison to selfreferred patients. The self-referred patients stayed closer to health facilities. This was probably the reason these patients decided to come to Hospital instead of going to their nearby PHC clinics. Conclusion: Findings of this study will be reported to the district and provincial department of health and hopefully will be used for improvement of maternal health services in the Dr Ruth Segomotsi Mompati District.
Keywords: Outcome Assessment (Health Care)